Biomass-derived aviation fuels: Challenges and perspective. (September 2019) - Wang, Meng; Dewil, Raf.; Maniatis, Kyriakos; Wheeldon, John; Tan, Tianwei; Baeyens, Jan; Fang, Yunming
Abstract: The worldwide utilization of fossil energy, including its specific application as transportation fuel, significantly contributes to the continuous increase of the atmospheric CO2 concentration. Several solutions have been promoted or scheduled to reduce CO2 emissions. Among these solutions, the development of renewable energy resources, such as bio-fuels, offers important advantages as promoted by several countries and institutions who disclosed their plans to partly or totally use alternative renewable energy sources in the future. For the rapidly growing aviation sector, aviation fuel derived from fossil resources is still the major available energy source. The development of renewable aviation fuel is considered to be a promising future strategy to reduce related CO2 emissions. The worldwide total aviation fuel consumption by commercial airlines increased from about 260 million m³/year in 2005 to over 340 million m³/year in 2018, and a further annual increase of about 5% is expected till 2050. Worldwide actions have hence been undertaken with respect to bio-aviation fuel production, distribution, and demonstration flying. As a relatively new topic, there are a lot of remaining challenges in technology development, fuel certification and distribution. The production technology, policy and environmental impact of bio-aviation fuel were comprehensively reviewed, including its production by the catalytic conversion of lipids, by the conversion of carbohydrates or lignocellulosic biomass, and by developing bio-refinery concepts for bio-aviation fuel production. The future reduction of CO2 emissions in the aviation sector requires an improvement of the biomass to aviation fuel production technology through the correct integration of biology, chemical engineering, and energy crops. The paper illustrates this potential integration through reviewing the current research in the production of aviation fuels from biomass, including the complete industrial chain from airplane manufacturer, aviation fuel producer and provider, airline strategies, and ongoing R&D, bearing in mind that major efforts are required to foster the development of the cost-effective production of renewable aviation fuel. The different topics of the Table of contents will be subsequently dealt with. Graphical abstract: Image, graphical abstract